Tradisi Layang-Layang Di Nagari Jopang Manganti, Warisan Budaya Yang Terus Mengudara - Halomoan .; Alan Pratama; Muhammad Iqbal; Yogi Ardian Hidayatullah; Zerian Jehan Alhadi; Hazel Putra Perdana (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
The kite tradition in Nagari Jopang Manganti, 50 Kota Regency, West Sumatra, represents a cultural heritage rich in historical, social, and philosophical values, and is a vital part of Minangkabau identity. Kites are not merely recreational games but serve as symbols of freedom bounded by customary and Islamic law (Adat basandi syarak, syarak basandi Kitabullah) and embody the harmony between humans and nature. Preservation of this tradition through festivals and mutual cooperation (gotong-royong) strengthens social solidarity, intergenerational transmission of ancestral values, and a dynamic, living cultural identity. Beyond entertainment, this tradition plays an important role in character education, fostering creativity, and cultivating local pride. The sustainability of the kite tradition requires continuous support from the community, traditional leaders, government, and cultural institutions to ensure its endurance amid modernization. This research employs a qualitative method with a folklore approach, utilizing interviews and observations, to reveal the social, cultural, and educational values embedded in the kite tradition in Nagari Jopang Manganti.